Class Attendance Management System Using NFC Mobile Devices. Issue 2 (3rd April 2017) - Mohandes, Mohamed A.
Abstract: Monitoring students' class attendance in any educational institution is an important process as it is directly linked to academic performance. Collecting the student attendance manually results in loss of precious time, and also delays in subsequent processing of the collected data. In order to help faculty members concentrate on teaching, a solution is proposed for automating, monitoring, and further processing attendance collection, This paper describes a prototype of Class Attendance Management System (CAMS) that has been developed and evaluated using an NFC enabled mobile device and an NFC (or RFID) tag/card. This system helps school/university faculty in taking attendance in a class using his/her mobile phone in a quick and simple way, thus saving precious time in a classroom. Faculty can monitor students' attendance throughout an academic term, issue warnings, and request withdrawal of a student due to poor attendance as per the policy of the institution. The application in the NFC enabled phone reads a student ID by simply tapping it against an NFC student ID card. The application depends on the NFC enabled Android devices to read the student campus card, and extract his ID number to be used as a student identifier in CAMS. The developed system has been evaluated at King Fahd University of Petroleum and Minerals, Saudi Arabia during two academic terms. Positive feedback has been obtained from faculty and administration.